KONSEP AUDITORI DALAM AL QURAN DAN APLIKASINYA DI DUNIA PENDIDIKAN - Victor Imaduddin Ahmad (Akademika, 2018)
Abstract: This study aims to formulate the concept of hearing in the Qur'an and how it is applied in education. From thematic studies it is found the concepts of hearing in the Quran as follows: (1) Hearing is the first and main sense in human development so that it becomes an important knowledge path. (2) From the study of auditory objects it is found appropriate guidance for certain different conditions. Qawlan Ma'rufa for public associations, qawlan sadi>da for childcare and learning, qawlan bali>gha for study, qawlan kari>ma for associations with parents and respectable people, ahsanu qaula for da'wah, qawlan tsaqila for da'wah callers, qawlan maysura for weak people the needy, qawlan layyinan for diplomacy. (3) There is an internal prohibition that will have a negative effect on listeners. Hearing fake news, tajassus, other people's ugliness and so on. (4) There is a prohibition on making statements resulting in sin and danger. Falsehood, qawlan adhi>ma which generally contains falsehood, or puns that contain ridicules, manna, adza, mocking others, self-deprecation, giving bad nicknames, vain words that cannot be understood ( 5) From the aspect of how to regulate intonation, the Quran also regulates a code of ethics and in a good way. The application of the concept of hearing in education can be done in the following five steps: (1) Preparing place and psychological conditions (2) Reading ta>wudz and basmalah (3) Providing the best example according to conditions (4) Students repeat correctly, (5) Delivering with true method in accordance with the so-called qawlan baligha.Keywords: Hearing, the Quran, education